Rheological properties of a novel cold asphalt mastic with fast curing by means of magnetic induction - Manuel Lagos-Varas; Christopher Delafuente-Navarro; Pedro Lastra-González; Feipeng Xiao; Daniel Castro-Fresno (Results in Engineering)
Curing time required by cold asphalt mixtures is quite long, what has induced researchers to develop a fast-curing method utilising magnetic induction. In this regard, this research evaluated the rheological consequences of the novel procedure on the mastic by comparison of two reference mastics: one cured following the U.S. Asphalt institute guidelines and another at room temperature for 7 days. In addition, a mastic made with a conventional polymer-modified binder (PMB) was considered as a control mastic. Rheological evaluation of the mastics was performed using the dynamic shear rheometer (DSR), multiple stress creep recovery (MSCR), dynamic shear rheometer-elastic recovery (DSR-ER), linear amplitude sweep (LAS) and binder yield energy (BYE). Burgers' mathematical model was used to develop the DSR-ER and MSCR results. It was found that the PMB mastic had the best performance in all tests. Whereas, all mastics made with asphalt emulsion, irrespective of the curing process, indicated low performance in terms of plastic deformation. Specifically, in terms of stiffness, accelerated curing by magnetic induction was more representative of what happened in real conditions, as oven curing leaded to premature ageing.